DEVELOPMENT OF VOLCANO SURFACE TEMPERATURE MEASUREMENT TELEMETRY SYSTEM USING FSK (FREQUENCY SHIFT KEYING) METHOD - Ihsudha, Husni
In the era of rapid technological development nowdays, one of the most developed technology is IoT (Internet of Thing). One weakness of this technology is application to be used for regions or places with certain condition that do not have internet connection. By taking a case of a mountainous area, this final project developed a telemetry device to measuring temperature using FSK (Frequency Shift Keying) method as a thermal monitoring device. In this final project a data acquisition and FSK modulator and demodulator are built. Data acquisition block was built using AD620 as an instrumentation amplifier added with LM358 as a non-inverting amplifier. FSK modulator is made using IC NE555 with PNP transistor as regulator of the input. The FSK modulator is built using LM565 PLL IC with addition LM710 as comparator. From the research that has been done, the data acquisition block can produce output voltage in the range of 0-5V for 10-80oC temperature range. These temperature range is chosen based on field data taken in July 2019 at Tangkuban Perahu Mount. From the data acquisition block, using Arduino nano digital signal can be made and containing ADC data information. The digital signal is modulated and produces a signal with two frequencies, 1,070kHz for bit 1 signals and 1,223kHz for bit 0 signals. These signals can be returned to digital signals using a demodulator with 5V voltage results for 1 bits and 1V for 0 bits.